Utilization of Used Rubber Bands as Sports Equipment for Skipping Rope - Pirdaus, Dede Irman; Yohandoko, Setyo Luthfi Okta; Lianingsih, Nestia (International Journal of Health, Medicine, and Sports, 2024)
This study explores the potential of reusing discarded rubber bands as an alternative material to create an affordable and environmentally friendly jump rope. The study emphasizes the importance of physical activity, particularly jump rope, for maintaining health and fitness. By utilizing discarded rubber bands, the study aims to address waste reduction and the need for accessible sports equipment. The methodology involves collecting, cleaning, and assembling discarded rubber bands into a functional jump rope. Fitness measurements, including resting heart rate, maximum jumps per minute, and time to exhaustion, were recorded before and after the exercise period. Results showed improvements in all measured parameters: decreased mean resting heart rate (from 72.4 to 68 bpm), increased maximum jumps per minute (from 84.8 to 110), and longer time to exhaustion (from 5.2 to 7.2 minutes). These findings suggest that the rubber band jump rope effectively contributed to the cardiovascular health, stamina, and endurance of the participants. The study concludes that the repurposed rubber band jump rope offers a viable, cost-effective, and environmentally friendly alternative to traditional sports equipment. This innovation has the potential to contribute to environmental sustainability, social inclusivity in fitness, and economic accessibility to sports equipment.